Comparative Evaluation of Salt Tolerance in Four Self-Rooted Hazelnut (Corylus avellana L. and Corylus americana Walter) Cultivars - Xavier Rius-Garcia; María Videgain-Marco; José Casanova-Gascón; Luis Acuña-Rello; Pablo Martín-Ramos (Agronomy)
Rising soil salinity poses a significant challenge to hazelnut cultivation, particularly in Mediterranean regions, where the increasing use of low-quality irrigation water necessitates the identification of salt-tolerant cultivars for sustainable production. This study investigated the salt tolerance mechanisms in four hazelnut cultivars (Barcelona, Tonda di Giffoni, Tonda Gentile Romana, and Yamhill) exposed to varying NaCl concentrations (0, 25, 50, and 75 mM) over five months. This research assessed their morphological, physiological, and biochemical responses through an analysis of their growth parameters, photosynthetic efficiency, visual symptoms, and ion content. The results revealed significant genotypic variation in their salt tolerance mechanisms. Tonda di Giffoni demonstrated superior salt tolerance, maintaining a higher photosynthetic efficiency and better ion balance, particularly in K⁺/Na⁺ and Ca2⁺/Na⁺ ratios. Barcelona showed moderate tolerance at lower salinity levels but declined sharply under higher stress. Yamhill exhibited a strong survival capacity despite its poor photosynthetic performance, while Tonda Gentile Romana proved most sensitive to salinity stress. All the cultivars showed a significant biomass reduction, with their fresh and dry weights decreasing by over 80% at 75 mM NaCl. Leaf chloride concentrations dramatically increased, reaching levels 481% higher than those in the control conditions. This study identifies Tonda di Giffoni as the most suitable cultivar for moderately saline conditions and provides insights into hazelnut salt tolerance mechanisms, contributing valuable information for breeding programs and cultivation strategies in salt-affected regions.